GE_GERICHTE P/9180/2022 vom 18. April 2023 - GE Cour de justice (2023)
CIRCULATION ROUTIÈRE(DROIT DE LA CIRCULATION ROUTIÈRE);DISPOSITIONS PÉNALES DE LA LCR | LCR.96.al1.letc; LCR.90.al1; LCR.30.al2; OCR.67.al1; LCR.100; CP.13